Inferring Airflow Across Martian Dunes From Ripple Patterns and Dynamics - Hood, D. R.; Ewing, R. C.; Roback, K. P.; Runyon, K.; Avouac, J.-P.; McEnroe, M. (Frontiers in Earth Science, 2021)
Large ripples form striking patterns on the slopes of martian sand dunes which can be mapped and tracked using high-resolution optical images. The ripples vary in orientation, wavelength, plan-view morphology, and rates of migration. The variations in the ripple patterns are recognized to signal the effects of the regional and local winds and feedbacks between winds and dune topography. We examine the ripple patterns and the motion of these ripples to interpret airflow dynamics around dunes in the dune field at Nili Patera. We find that coincident changes in ripple patterns and migration rates in dune wakes indicate reattachment lengths of 4–7 brink heights. This reattachment length is similar to length scales of flow reattachment for airflow over dunes measured on Earth despite the differences in aeolian environment. Furthermore, ripples on dune flanks are shown to behave according to terrestrial models for ripple development on steep slopes. Compensating for these slope effects allows them to act as indicators of dune-modified and regional wind directions. Changes in ripple patterns and migration rates also signal the response of dunes and airflow during dune collisions. Collectively, we find that differences in ripple patterns connected to changes in migration rate provide information on airflow over and around dunes. This detailed assessment of ripple measurement and ripple migration rates advances the use of ripples on martian dunes and sand sheets to infer dune- and field-scale wind dynamics. These measurements also indicate that the low density atmosphere on Mars does not significantly modify the behavior of wind-topography interactions compared to Earth. Such observations provide targets for computational fluid dynamic and large-eddy simulation models seeking to reveal complex airflows across dune fields both on Earth and on Mars.